2009
DOI: 10.1093/imrn/rnp019
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Inequalities and Generalized Ricci Bounds in the Heisenberg Group

Abstract: We prove that no curvature-dimension bound CD(K, N) holds in any Heisenberg group Hn. On the contrary the measure contraction property M CP (0, 2n + 3) holds and is optimal for the dimension 2n + 3. For the non-existence of a curvature-dimension bound, we prove that the generalized "geodesic" Brunn-Minkowski inequality is false in Hn. We also show in a new and direct way, (and for all n ∈ N\{0}) that the general "multiplicative" Brunn-Minkowski inequality with dimension N > 2n + 1 is false.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(128 citation statements)
references
References 24 publications
4
123
0
1
Order By: Relevance
“…Note also that, under the same assumptions as in Theorem 1.1, it was shown in [10] that (M, d CC , vol P ) satisfies MCP (0, 2n + 3), where d CC is the Carnot-Caratheordory distance and vol P is the Popp measure (see also [8,1] for the earlier results).…”
Section: Introductionmentioning
confidence: 86%
“…Note also that, under the same assumptions as in Theorem 1.1, it was shown in [10] that (M, d CC , vol P ) satisfies MCP (0, 2n + 3), where d CC is the Carnot-Caratheordory distance and vol P is the Popp measure (see also [8,1] for the earlier results).…”
Section: Introductionmentioning
confidence: 86%
“…The point is that u c z (η(t)) is not proportional to t since (u c z • η) (t) = c+L(η(t)) and L(η) is not necessarily constant. We also remark that even the stronger inequality (6.2) does not imply the curvature bound Ric [57,Remark 5.6] for a simple example, and [27] for a related work on the gap between the measure contraction property and the curvature-dimension condition in Heisenberg groups).…”
Section: Laplacian Comparisonmentioning
confidence: 94%
“…This approach has also been conducted on the Heisenberg group [Jui09]: no Ricci curvature lower bound CD(K, N ) with K > −∞ holds in this space. On the other hand, in [Jui09] it is shown that a related but weaker property holds, the measure contraction property [Stu06,Oht07].…”
Section: Nmentioning
confidence: 99%
“…On the other hand, in [Jui09] it is shown that a related but weaker property holds, the measure contraction property [Stu06,Oht07].…”
Section: Nmentioning
confidence: 99%